Pre-exposure prophylaxis access in federally qualified health centers across 11 United States metropolitan statistical areas. (September 2019) - Tookes, Hansel; Yao, Kristiana; Chueng, Teresa; Butts, Stefani; Karsner, Ryan; Duque, Maria; Cardenas, Gabriel; Feaster, Daniel J; Doblecki-Lewis, Susanne
Pre-exposure prophylaxis (PrEP) is a promising tool for HIV prevention, but uptake has been slow in key demographics and geographic areas including racial and ethnic minorities. Federally qualified health centers (FQHCs), serving those with heightened risk of contracting HIV, including low-income and minority patients regardless of ability to pay, are potential sites for PrEP delivery. This study aims to determine availability of PrEP at FQHCs in the US. FQHCs in the 11 largest U.S. metropolitan statistical areas (MSAs) were included. The south included Atlanta, Dallas, District of Columbia, Houston, and Miami. Reference MSAs included Boston, Chicago, Los Angeles, New York, Philadelphia, and San Francisco. We randomly selected 360 FQHCs for phone calls in which investigators queried the availability of PrEP for HIV prevention at each center. The study was powered to determine a 10% difference in proportion of clinics with PrEP services by region. We used a bivariate logistic regression to compare cities and regions. The percentage of FQHCs providing PrEP generally was low within this sample, with 0–28.0% offering PrEP services in the southern and 14.0–33.3% in reference metropolitan areas. Overall, 19.3% of clinics sampled indicated that they offered PrEP. Logistic regression did not show any difference between southern and reference regions (p = 0.779). However, the total number of FQHCs was significantly lower in southern metropolitan areas (p = 0.014). FQHCs in all metropolitan areas provided limited access to PrEP. Interventions, including technical assistance to increase PrEP availability in these settings catering to underserved populations, could be beneficial.